Analisis Pengaruh Kompensasi Dan Kepuasan Kerja Terhadap Produktivitas Kerja Bidang Kesekretariatan PUPR Kabupaten Banggai : Analysis of The Influence of Compensation and Job Satisfaction on Work Productivity in The Government Secretariat of Banggai District PUPR - Ichsan Milang; Suwardi Zakaria; Ariska (Fakultas Ekonomi, Universitas Tompotika Luwuk, 2025)
The Department of Public Works and Spatial Planning is the agency responsible for public works and housing affairs. This research aims to determine the effect of compensation and job satisfaction on employee productivity at the secretariat office of the Department of Public Works and Spatial Planning of Banggai Regency. The type of data used is qualitative that has been quantified. The population consists of 16 people. The method used is Multiple Linear Regression Analysis, with the regression result Y = 19.966 + - 0.547 - 0.475 + e. The Correlation Coefficient is 0.584. The Coefficient of Determination in this study is 0.341, and the remaining variation is caused by other factors not included in this study. The t-value for (X1) is -1.850 < t-table 1.771.This means that the variable Compensation (X1) does not have a significant effect on Work Productivity (Y), thus H0 is accepted and Ha is rejected. The calculated t-value for (X2) is 2.288. The result of the t-test shows that 2.288 > 1.771. This indicates that the variable Job Satisfaction (X2) has a partial and significant effect on Work Productivity (Y), therefore H0 is rejected and Ha is accepted. Based on the results of the F-test, the calculated F-value is 3.365 > the table F-value of 3.81. This means H0 is rejected and Ha is accepted. Compensation (X1) and Job Satisfaction (X2) have a simultaneous or joint effect on Work Productivity (Y).